Les sociétés balkaniques et la guerre des mondes - Jean-François Gossiaux (Diasporas: Circulations, Migrations, Histoire)
Located at the crossroads of three worlds, the Occident and the two Orients, the Balkans have passed the last century between war and peace – the peace of the societies and the war between communities. The recent conflicts have been frequently interpreted by direct or indirect players on the mode of “Clash of Civilizations” theorized by Huntington. As a matter of fact, it is essentially “the Occident”, as civilization or imagined community, that gave to the Yugoslav wars their Huntingtonian dimension.